2018
DOI: 10.5098/hmt.10.4
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and Dufour Effects on Laminar Flow of a Rotating Fluid Past a Porous Plate in Conducting Field

Abstract: A theoretical investigation has been performed to describe the laminar flow of a rotating fluid past a porous plate in conducting field with variable temperature and variable concentration taking into account the chemical reaction, radiation and Dufour effects. The non-dimensional governing equations are solved numerically by using finite difference scheme. The effects of different physical parameters on velocity, temperature and concentration are presented and discussed with the help of graphs. Also the numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The study of the MHD flow of Maxwell nanofluid past a porous medium in the presence of radiation and chemical reaction was done by Reddy and Lakshminarayana 15 . Also, Reddy et al 16 have investigated heat radiation and the Dufour phenomenon's combined effect on a rotating flow past a permeable plate. Patel et al 17 have considered the MHD flow of micropolar Fe 3 O 4 –water nanofluid along an elongating or contracting sheet in the presence of radiation, thermophoresis, and Brownian motion.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the MHD flow of Maxwell nanofluid past a porous medium in the presence of radiation and chemical reaction was done by Reddy and Lakshminarayana 15 . Also, Reddy et al 16 have investigated heat radiation and the Dufour phenomenon's combined effect on a rotating flow past a permeable plate. Patel et al 17 have considered the MHD flow of micropolar Fe 3 O 4 –water nanofluid along an elongating or contracting sheet in the presence of radiation, thermophoresis, and Brownian motion.…”
Section: Introductionmentioning
confidence: 99%
“…Habib-OlahSayehvand et al (2017) have been documented that MHD nanofluid flow with viscous dissipation and joule heating through a permeable channel. Ananda Reddy et al (2018) examined that the radiation and dufour effects on laminar flow of a rotating fluid past a porous plate in conducting field. Rashad et al (2018) have been investigated that mixed bioconvection flow of a nanofluid containing gyrotactic microorganisms past a vertical slender cylinder.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Muthucumaraswamy et al [7] investigated transverse velocity. Ananda Reddy et al [8] discussed the rotating fluid with ramped wall temperature. It is observed that the temperature and velocity are lower at the ramped temperature plate than the isothermal plate.…”
Section: Introductionmentioning
confidence: 99%